Aspek Hukum Pelaksanaan Prinsip UNIDROIT dalam Kontrak Perdagangan Internasional di Indonesia - Desriyalni, Rizka; Ferdi, Ferdi; Delfiyanti, Delfiyanti; Elvardi, Jean (Universitas Ekasakti, 2023)
Differences in legal systems between countries give rise to various basic rules regarding international trade contracts. Efforts made to harmonize this were by holding an international convention by The International Institute for the Unification of Private Law (UNIDROIT) which gave birth to The UNIDROIT Principles of International Commercial Contracts (UPICCs). UPICCs are actually used as a legal basis for implementing international trade contracts. The formulation of the research problem is how is the principle of freedom of contract, the principle of good faith and fair dealing regulated in international law and national law?, and what are the challenges of implementing the UNIDROIT principle in international trade contracts in Indonesia? ? This research is normative legal research and is analytical descriptive. The results of the research are that international law regulations regarding the principle of freedom of contract, the principle of good faith and fair dealing are regulated by UPICCs. Meanwhile, regulations in national law can be seen in the Civil Code and the ITE Law. S Because the UPICCs regulate many matters that are not detailed in Book III of the Civil Code, the challenge is the unification and codification of contract law to provide legal certainty, with uniform provisions that can be universally accepted by countries involved in international trade.